In vivo and in vitro induction of human cytochrome P4503A4 by dexamethasone - McCune, J S; Hawke, R L; LeCluyse, E L; Gillenwater, H H; Hamilton, G; Ritchie, J; Lindley, C (Clinical pharmacology and therapeutics, 2000)
The aims of these experiments were to determine the effect of a therapeutic regimen of dexamethasone on cytochrome P4503A4 (CYP3A4) activity in healthy volunteers; and the concentration-effect relationship between dexamethasone and CYP3A4 activity in primary human hepatocyte cultures. The effect of dexamethasone (8 mg administered by mouth two times a day for 5 days) on CYP3A4 activity in 12 healthy volunteers was assessed with the erythromycin breath test and urinary ratio of dextromethorphan to 3-methoxymorphinan. Concentration-effect of dexamethasone on CYP3A4-dependent testosterone 6-beta-hydroxylation was determined in human hepatocytes treated with 2 to 250 micromol/L dexamethasone. The percent of erythromycin metabolized per hour increased from 2.20% +/- 0.60% (mean +/- SD) at baseline to 2.67% +/- 0.55% on day 5 of dexamethasone (mean increase in hepatic CYP3A4 activity 25.7% +/- 24.6%; P = .004). The mean urinary ratio of dextromethorphan to 3-methoxymorphinan was 28 (4.8 to 109) and 7 (1 to 23) at baseline and on day 5 of dexamethasone (mean decrease = 49%; P = .06). Substantial intersubject variability was observed in the extent of CYP3A4 induction. The extent of CYP3A4 induction was inversely correlated with baseline erythromycin breath test (r2 = 0.58). In hepatocytes, dexamethasone 2 to 250 micromol/L resulted in an average 1.7-fold to 6.9-fold increase in CYP3A4 activity, respectively. The extent of CYP3A4 induction with dexamethasone in hepatocyte preparations was inversely correlated with baseline activity (r2 = 0.59). These data demonstrate that dexamethasone at doses used clinically increased CYP3A4 activity with extensive intersubject variability and that the extent of CYP3A4 induction was, in part, predicted by the baseline activity of CYP3A4 in both healthy volunteers and human hepatocyte cultures.